Transparent flame-retardant polymethyl methacrylate composite material and preparation method thereof
Preparation by using modified hexaphenoxycyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene as flame retardant, combined with acrylate rubber grafted methyl acrylate and coupling agent, It has produced a transparent flame-retardant PMMA composite material with excellent mechanics, flame retardant and transparent properties, which solves the problems of both flame retardant performance and transparency in the prior art, and realizes the feasibility and environmental protection of industrial applications.
Patent Information
- Application Number
- CN202411831323.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively improve its flame retardant properties while maintaining the transparency and mechanical properties of polymethyl methacrylate (PMMA), especially in industrial applications.
Modified hexaphenoxycyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene are used as flame retardants, through the coordination of grafting methyl methyl acrylate and coupling agent with acrylate rubber By function, transparent flame retardant PMMA composite material with excellent mechanical, flame retardant and transparent properties were prepared.
It has achieved high flame retardant performance, excellent mechanical properties and good transparency of polymethyl methacrylate composite materials. It is suitable for the field of halogen-free flame retardant transparent electronics and electrical appliances, and simplifies the process and reduces production costs.
Smart Images

Figure BDA0005185621780000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plastic materials, and in particular to a transparent flame-retardant polymethyl methacrylate composite material and a preparation method thereof. Background Art
[0002] Polymethyl methacrylate (PMMA), also known as "organic glass", is a polymer material with excellent optical properties. It has good electrical insulation, wear resistance and weather resistance, and is widely used in aerospace, mobile communications, transportation and other fields. However, PMMA itself has poor heat resistance and is a very flammable material. Its peak heat release rate (PHRR) in the cone calorimetry test can be as high as 1058kW / m 2 , and the combustion process of PMMA is often accompanied by severe dripping. Once burned, it will cause great harm. Therefore, the research on PMMA flame retardant modification is of great significance. The commonly used method is to blend PMMA with flame retardants to obtain flame retardant PMMA, but this method usually sacrifices the transparency of PMMA, which significantly limits its application in the optical field; another method is to connect the flame retardant monomer to the PMMA molecular chain by copolymerization. This method has little effect on the light transmittance of PMMA, but flame retardants containing flame retardant elements and unsaturated carbon-carbon double bonds often require a series of complex chemical reactions for preparation, which is costly and limits its large-scale industrial application. Therefore, the research and development of simple, easy-to-obtain, cost-effective transparent flame retardant PMMA is a huge challenge that needs to be solved in the current PMMA modification. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present application provides a transparent flame-retardant polymethyl methacrylate composite material and a preparation method thereof. The transparent flame-retardant polymethyl methacrylate composite material prepared in the present application has excellent mechanical properties, flame-retardant properties and transparency properties, and can be widely used in the field of electronic appliances that require halogen-free flame-retardant transparency. In addition, the preparation method of the present application has a simple process, is easy to control, and is conducive to industrial production.
[0004] In a first aspect, the present application provides a transparent flame-retardant polymethyl methacrylate composite material, which adopts the following technical solution: A transparent flame-retardant polymethyl methacrylate composite material comprises the following raw materials, measured by weight: 75-82 parts of polymethyl methacrylate, 15-20 parts of acrylate rubber grafted methyl acrylate, 15-18 parts of a flame retardant, 4-7 parts of a toughening agent, 1-1.5 parts of a coupling agent, 0.3-0.5 parts of an antioxidant, and 0.3-0.5 parts of a lubricant, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene.
[0005] By adopting the above technical scheme, polymethyl methacrylate: as the main component of the composite material, it provides good weather resistance, transparency, surface hardness and processability. Acrylate rubber grafted methyl acrylate: as a toughening agent, it improves the toughness of the composite material without affecting the light transmittance of the material. Its double-layer shell-core structure helps to improve the mechanical properties and transparency of the material. Flame retardant: prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene. These two substances improve the flame retardant properties of the composite material through synergistic effect. The modified hexaphenoxy cyclotriphosphazene and hexa(4-aminophenoxy)cyclotriphosphazene are modified by silane coupling agent and nano-silica to improve the dispersibility and compatibility with other components. Toughening agent: further improves the toughness of the material, making it less likely to have the risk of assembly cracking during use. Improved compatibility between the raw materials helps to improve the overall performance of the composite material. Antioxidant: prevents the material from deteriorating or failing due to oxidation during storage and use. Lubricant: Reduce the friction coefficient of the material surface and improve the processing and use performance of the material. These raw materials work together to make the prepared transparent flame-retardant polymethyl methacrylate composite material have excellent mechanical properties, flame retardant properties and transparency properties, and are suitable for the field of electronic appliances that require halogen-free flame retardancy and transparency.
[0006] Preferably, the mass ratio of the modified hexaphenoxy cyclotriphosphazene to the modified hexa(4-aminophenoxy)cyclotriphosphazene is 4:2-4.
[0007] By adopting the above technical scheme, the flame retardant properties of polymethyl methacrylate composite materials are improved by compounding modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene, mainly through the synergistic flame retardant effect of organic phosphorus-nitrogen and nano-silicon dioxide. At the same time, the modified hexaphenoxy cyclotriphosphazene and the modified hexa(4-aminophenoxy)cyclotriphosphazene are first modified by a silane coupling agent and then by nano-silicon dioxide, which greatly improves their dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of polymethyl methacrylate composite materials. Hexaphenoxy cyclotriphosphazene belongs to a phosphorus-nitrogen flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant properties and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion, and is particularly suitable for flame retardant electrical materials. Moreover, hexaphenoxy cyclotriphosphazene can be chemically grafted onto the surface of nano-silica particles after being modified by a silane coupling agent to prepare a new type of phosphorus-nitrogen-containing nano flame retardant, and applied to a polymethyl methacrylate composition. Since the silica nanoparticles can significantly improve the combustion properties of the polymer, such as the heat release rate, the organic phosphorus-nitrogen and the nanoparticles have an obvious synergistic flame retardant effect. At the same time, the refractive index of the grafted silica nanoparticles is 1.48-1.49, which is close to the refractive index of the polymethyl methacrylate resin (1.49), so it has no effect on the light transmittance of the polymethyl methacrylate composite material. The modified hexa(4-aminophenoxy)cyclotriphosphazene has an organic-inorganic hybrid structure with alternating single and double bonds of phosphorus and nitrogen, which can play a good synergistic flame retardant role; each phosphorus atom in the phosphazene molecule has two active PN bonds, which has good designability and can synthesize different phosphazene structures. The ring-crosslinked phosphazene compounds formed have various forms such as nanofibers, hollow spheres, and layered structures; due to the small size effect and high specific surface area of nanomaterials, nanomaterials greatly improve the flame retardant properties of polymethyl methacrylate composites. In summary, the modified hexaphenoxycyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene significantly improve the flame retardant properties, mechanical properties and transparency of the composite materials through their unique structure and synergistic effect, making them suitable for the field of electronic and electrical appliances that require halogen-free flame retardancy and transparency.
[0008] Preferably, the preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31, according to the mass parts, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours, then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then after reacting for 10-12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S32. Dry the nano-silica with a particle size of 20-30 nm at 100-120°C for 6-8h according to the mass fraction, then add 250 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20h under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
[0009] By adopting the above technical scheme, hexaphenoxy cyclotriphosphazene belongs to phosphorus-nitrogen flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant performance and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion, and is particularly suitable for flame retardant of electrical materials. In addition, hexaphenoxy cyclotriphosphazene can be chemically grafted to the surface of nano-silica particles after modification by silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and applied to polymethyl methacrylate composition. Since silica nanoparticles can significantly improve the combustion performance of polymers such as heat release rate, organic phosphorus-nitrogen and nanoparticles have obvious synergistic flame retardant effect. At the same time, the refractive index of the grafted silica nanoparticles is 1.48-1.49, which is close to the refractive index of polymethyl methacrylate resin (1.49), so it has no effect on the light transmittance of polymethyl methacrylate composite materials.
[0010] Preferably, the preparation method of the modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41, according to the mass parts, add 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate to 2500 parts of acetone and mix them evenly, then react at a temperature of 70-75° C. for 48-52 hours under nitrogen protection, then pour the reacted material into deionized water, stir, filter, collect the obtained solid, wash it with deionized water, n-hexane and ethanol in turn, place it in a vacuum drying oven at a temperature of 60-70° C. and dry it for 40-48 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of 43% sodium hydroxide aqueous solution are mixed uniformly, and the mixture is heated to 85-90° C. and reacted for 40-48 hours at a stirring rate of 100 rpm, and the reacted material is cooled to room temperature, filtered, and the solid is washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and the temperature is raised to 75-80°C under nitrogen protection, and the temperature is kept for 0.7-1h, then 0.3 parts of azobisisoheptanenitrile are dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1h, and then after reacting for 10-12h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. According to the mass fraction, nano-silica with a particle size of 20-30 nanometers is dried at 100-120°C for 6-8 hours, and then 80 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene are added to 500 parts of anhydrous ethanol. After stirring evenly, reflux the reaction at 78-82°C for 10-12 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.
[0011] By adopting the above technical scheme, the prepared modified hexa(4-aminophenoxy)cyclotriphosphazene has an organic-inorganic hybrid structure with alternating single and double bonds of phosphorus and nitrogen, which can play a good synergistic flame retardant role; each phosphorus atom in the phosphazene molecule has two active PN bonds, which has good designability and can synthesize different phosphazene structures. The ring-crosslinked phosphazene compounds formed have various forms such as nanofibers, hollow spheres, and layered structures; due to the small size effect and high specific surface area of nanomaterials, nanomaterials greatly improve the flame retardant properties of polymethyl methacrylate composite materials. At the same time, the modified hexa(4-aminophenoxy)cyclotriphosphazene is first modified by a silane coupling agent and then by nano-silicon dioxide, which greatly improves its dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of the polymethyl methacrylate composite material.
[0012] Preferably, the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 3:1-3.
[0013] By adopting the above technical scheme, the coupling agent plays a vital role in the preparation process of the composite material. It is mainly used to improve the compatibility between different materials and improve the performance of the material. In the present application, the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 3:1-3. These two compounds can improve the mechanical properties and flame retardant properties of polymethyl methacrylate composite materials through synergistic action. γ-(methacryloyloxy)propyltrimethoxysilane has good bonding properties and chemical activity. It can react with modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene to form a stable chemical bond, thereby improving the dispersibility of these flame retardants and compatibility with other components. Vinyltriethoxysilane has good reactivity and bonding properties. In the present application, it can react with polymethyl methacrylate and other components to improve the mechanical properties and flame retardant properties of the composite material. In general, γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane can improve the mechanical properties and flame retardant properties of polymethyl methacrylate composites through synergistic effects. At the same time, they can also improve the dispersibility of flame retardants and their compatibility with other components, thereby further improving the transparency of the composites.
[0014] Preferably, the acrylate rubber grafted methyl acrylate is a double-layer shell-core structure, wherein the first shell is acrylate, the second shell is a rubber layer, and the inner core is a methyl acrylate solid core; the refractive index of the acrylate rubber grafted methyl acrylate is 1.49.
[0015] By adopting the above technical scheme, polymethyl methacrylate has the characteristics of excellent weather resistance, good transparency and appearance, high surface hardness, good processability, etc., and is widely used in various fields. However, its disadvantage is that the material toughness is poor, and there is a risk of assembly cracking during use. By adopting acrylate rubber grafted with methyl methacrylate, not only the toughness of polymethyl methacrylate composite materials can be improved, but also its light transmittance has no effect. This is because acrylate rubber grafted with methyl methacrylate is a double-layer shell-core structure, in which the first shell is acrylate, the second shell is a rubber layer, and the inner core is a methyl methacrylate solid core, whose refractive index is 1.49, which is consistent with the refractive index of polymethyl methacrylate resin.
[0016] Preferably, the number average relative molecular mass of the polymethyl methacrylate is 27000-33000.
[0017] Preferably, the toughening agent is butadiene grafted acrylate styrene copolymer.
[0018] Preferably, the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite; and the lubricant is selected from glyceryl stearate.
[0019] In a second aspect, the present application provides a method for preparing a transparent flame-retardant polymethyl methacrylate composite material, which adopts the following technical solution: As a general technical concept, the present application also provides a method for preparing the transparent flame-retardant polymethyl methacrylate composite material, comprising the following steps: S101, mixing polymethyl methacrylate, acrylate rubber grafted methyl acrylate, flame retardant, toughening agent, coupling agent, antioxidant and lubricant in parts by mass to obtain a premix; S102, melt-extrude the premix at an extrusion temperature of 210-220° C. in a twin-screw extruder, cool and granulate to obtain a transparent flame-retardant polymethyl methacrylate composite material.
[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. Excellent mechanical properties: By using materials such as acrylate rubber grafted methyl acrylate and modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene, the toughness of the composite material is significantly improved while maintaining good light transmittance.
[0021] 2. Excellent flame retardant properties: The synergistic flame retardant effect of modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene makes the composite material have higher flame retardant properties.
[0022] 3. Good transparency: The structural design of acrylate rubber grafted with methyl acrylate ensures that the light transmittance of the composite material is not affected. At the same time, the refractive index of the modified silica nanoparticles is similar to that of polymethyl methacrylate resin, which further ensures the transparency of the material.
[0023] 4. Feasibility of industrial production: The preparation method is simple and easy to control, which is conducive to industrial production.
[0024] 5. Environmental protection and safety: The use of halogen-free flame retardants reduces potential harm to the environment and human health. DETAILED DESCRIPTION
[0025] The implementation scheme of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially, polymethyl methacrylate, number average molecular weight of 29000, purchased from Chi Mei Industrial Co., Ltd., Taiwan, China; acrylate rubber grafted methyl acrylate methyl acrylate, purchased from Kaneka Chemical Industry Co., Ltd., Japan; toughening agent: butadiene grafted acrylate styrene copolymer, purchased from Kaneka Chemical Industry Co., Ltd., Japan, model: M-210.
[0026] In the following examples and preparation examples, 1 part means 100 g.
[0027] Preparation Example 1 Preparation of modified hexaphenoxy cyclotriphosphazene The preparation method of modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the temperature is raised to 78° C. under nitrogen protection, and the temperature is kept for 1.2 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour. After reacting for 11 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S32. According to the mass proportions, nano-silica with an average particle size of 20 nanometers is dried at 110°C for 7 hours, and then 250 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene are added to 1500 parts of anhydrous ethanol. After stirring evenly, reflux the mixture at 80°C for 18 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
[0028] Preparation Example 2 Preparation of modified hexa(4-aminophenoxy)cyclotriphosphazene The preparation method of modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41. According to the mass fractions, 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate are added to 2500 parts of acetone and mixed evenly, and then reacted at a temperature of 73° C. for 50 hours under nitrogen protection, and then the reacted material is poured into deionized water, stirred, filtered, and the solid is collected and washed with deionized water, n-hexane and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 65° C. for 44 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of a 43% sodium hydroxide aqueous solution were mixed uniformly, and the mixture was heated to 88° C. and reacted for 46 hours at a stirring rate of 100 rpm. The reacted material was cooled to room temperature, filtered, and the solid was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and the temperature is raised to 78° C. under nitrogen protection, and the temperature is kept for 0.8 h, then 0.3 parts of azobisisoheptanenitrile is dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 h, and then after reacting for 11 h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. According to the mass proportion, nano-silica with an average particle size of 20 nanometers is dried at 110°C for 7 hours, and then 80 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene are added to 500 parts of anhydrous ethanol. After stirring evenly, reflux the mixture at 80°C for 11 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.
[0029] Example 1 A transparent flame-retardant polymethyl methacrylate composite material comprises the following raw materials, measured by weight: 75 parts of polymethyl methacrylate, 15 parts of acrylate rubber grafted methyl acrylate, 15 parts of flame retardant, 4 parts of butadiene grafted acrylate styrene copolymer, 1 part of coupling agent, 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.3 parts of stearic acid glycerol, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:2; and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 3:1.
[0030] The method for preparing the transparent flame-retardant polymethyl methacrylate composite material comprises the following steps: S101, according to the mass proportions, polymethyl methacrylate, acrylate rubber grafted methyl acrylate, flame retardant, butadiene grafted acrylate styrene copolymer, coupling agent, bis(2,4-dicumylphenyl)pentaerythritol diphosphite and glyceryl stearate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 210° C. in a twin-screw extruder, setting the screw speed in the range of 400 rpm, and cooling and granulating after extrusion to obtain a transparent flame-retardant polymethyl methacrylate composite material.
[0031] Example 2 A transparent flame-retardant polymethyl methacrylate composite material comprises the following raw materials, measured by weight: 82 parts of polymethyl methacrylate, 20 parts of acrylate rubber grafted methyl acrylate, 18 parts of flame retardant, 7 parts of butadiene grafted acrylate styrene copolymer, 1.5 parts of coupling agent, 0.5 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.5 parts of stearic acid glycerol, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:4; and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 3:3.
[0032] The method for preparing the transparent flame-retardant polymethyl methacrylate composite material comprises the following steps: S101, according to the mass proportions, polymethyl methacrylate, acrylate rubber grafted methyl acrylate, flame retardant, butadiene grafted acrylate styrene copolymer, coupling agent, bis(2,4-dicumylphenyl)pentaerythritol diphosphite and glyceryl stearate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 220° C. in a twin-screw extruder, setting the screw speed in the range of 400 rpm, and cooling and granulating after extrusion to obtain a transparent flame-retardant polymethyl methacrylate composite material.
[0033] Example 3 A transparent flame-retardant polymethyl methacrylate composite material comprises the following raw materials, measured by weight: 78 parts of polymethyl methacrylate, 18 parts of acrylate rubber grafted methyl acrylate, 17 parts of a flame retardant, 6 parts of a butadiene grafted acrylate styrene copolymer, 1.3 parts of a coupling agent, 0.4 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.4 parts of stearic acid glycerol, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:3; and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 3:2.
[0034] The method for preparing the transparent flame-retardant polymethyl methacrylate composite material comprises the following steps: S101, according to the mass proportions, polymethyl methacrylate, acrylate rubber grafted methyl acrylate, flame retardant, butadiene grafted acrylate styrene copolymer, coupling agent, bis(2,4-dicumylphenyl)pentaerythritol diphosphite and glyceryl stearate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 215° C. in a twin-screw extruder, setting the screw speed in the range of 400 rpm, and cooling and granulating after extrusion to obtain a transparent flame-retardant polymethyl methacrylate composite material.
[0035] Comparative Example 1 The same as Example 3, except that: 96 parts of polymethyl methacrylate, 0 parts of acrylate rubber grafted methyl acrylate.
[0036] Comparative Example 2 The same as Example 3, except that: the flame retardant is modified hexaphenoxy cyclotriphosphazene.
[0037] Comparative Example 3 The same as Example 3, except that: the flame retardant is modified hexa(4-aminophenoxy)cyclotriphosphazene.
[0038] Comparative Example 4 The same as Example 3, except that: the coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane.
[0039] Comparative Example 5 The same as Example 3, except that: the coupling agent is vinyl triethoxy silane.
[0040] Performance testing The transparent flame-retardant polymethyl methacrylate composite materials prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 5 were sampled and injection-molded into test strips. The following tests were performed. The results are shown in Table 1.
[0041] Tensile strength: tested according to GB / T1040-2006 standard, the tensile rate is 50mm / min; Notched impact strength: tested according to GB / T1843-2008 standard; Flame retardant performance (limiting oxygen index): According to GB / T2406.2-2009 standard test, the limiting oxygen index of the sample is measured using an oxygen index meter, and the sample size is 150mm*6.5mm*3mm; Light transmittance: The sample was injection molded into a 80mm*50mm*2mm sample, and the light transmittance of the sample was tested using a light transmittance tester in accordance with the test standard GB / T 2410-2008.
[0042] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The transparent flame-retardant polymethyl methacrylate composite materials prepared in Examples 1 to 3 have excellent mechanical properties, flame-retardant properties and transparency properties, and can be widely used in the field of electronic appliances that require halogen-free flame-retardant and transparent properties.
[0043] 2) The performance comparison analysis of the transparent flame-retardant polymethyl methacrylate composite material prepared in Example 3 and Comparative Example 1 shows that the addition of acrylate rubber grafted methyl acrylate can not only improve the toughness of the polymethyl methacrylate composite material, but also has no effect on its light transmittance. This is because the acrylate rubber grafted methyl acrylate is a double-layer shell-core structure, in which the first shell is acrylate, the second shell is a rubber layer, and the inner core is a methyl acrylate solid core, whose refractive index is 1.49, which is consistent with the refractive index of polymethyl methacrylate resin.
[0044] 3) The performance comparison analysis of the transparent flame-retardant polymethyl methacrylate composite material obtained in Example 3 and Comparative Examples 2-3 shows that the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a mass ratio of 4:3, mainly through the synergistic flame retardant effect of organic phosphorus-nitrogen and nano-silicon dioxide. At the same time, the modified hexaphenoxy cyclotriphosphazene and the modified hexa(4-aminophenoxy)cyclotriphosphazene are first modified by a silane coupling agent and then modified by nano-silicon dioxide, which greatly improves their dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of the polymethyl methacrylate composite material. The unique structure and synergistic effect of modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene significantly improve the flame retardant properties, mechanical properties and transparency of the composite material, making it suitable for the field of electronic appliances that require halogen-free flame retardancy and transparency.
[0045] 4) The performance comparison analysis of the transparent flame-retardant polymethyl methacrylate composite material obtained in Example 3 and Comparative Examples 4-5 shows that the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 3:2, which is used to improve the compatibility between different materials and improve the performance of the material. The synergistic effect of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane can improve the mechanical properties and flame retardant properties of the polymethyl methacrylate composite material. At the same time, they can also improve the dispersibility of the flame retardant and the compatibility with other components, thereby further improving the transparency of the composite material.
[0046] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A transparent flame-retardant polymethyl methacrylate composite material, characterized in that: The preparation raw materials include, by weight: 75-82 parts of polymethyl methacrylate, 15-20 parts of acrylate rubber grafted methyl acrylate, 15-18 parts of flame retardant, 4-7 parts of toughening agent, 1-1.5 parts of coupling agent, 0.3-0.5 parts of antioxidant and 0.3-0.5 parts of lubricant, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene.
2. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The mass ratio of the modified hexaphenoxy cyclotriphosphazene to the modified hexa(4-aminophenoxy)cyclotriphosphazene is 4:2-4.
3. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the mixture is heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution. The azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then the mixture is reacted for 10-12 hours, and the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene. S32. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 250 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
4. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The preparation method of the modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41, according to the mass parts, add 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate to 2500 parts of acetone and mix them evenly, then react at a temperature of 70-75° C. for 48-52 hours under nitrogen protection, then pour the reacted material into deionized water, stir, filter, collect the obtained solid, wash it with deionized water, n-hexane and ethanol in turn, place it in a vacuum drying oven at a temperature of 60-70° C. and dry it for 40-48 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of 43% sodium hydroxide aqueous solution are mixed uniformly, and the mixture is heated to 85-90° C. and reacted for 40-48 hours at a stirring rate of 100 rpm, and the reacted material is cooled to room temperature, filtered, and the solid is washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and heated to 75-80°C under nitrogen protection, and kept warm for 0.7-1h, then, 0.3 parts of azobisisoheptanenitrile are dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1h, and then after reacting for 10-12h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 80 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene to 500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 10-12 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.
5. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 3:1-3.
6. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The acrylate rubber grafted methyl acrylate is a double-layer shell-core structure, wherein the first shell is acrylate, the second shell is a rubber layer, and the inner core is a methyl acrylate solid core; the refractive index of the acrylate rubber grafted methyl acrylate is 1.
49.
7. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The number average relative molecular mass of the polymethyl methacrylate is 27000-33000.
8. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The toughening agent is butadiene grafted acrylate styrene copolymer.
9. The transparent flame-retardant polymethyl methacrylate composite material according to claim 1, characterized in that: The antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite; and the lubricant is selected from glyceryl stearate.
10. A method for preparing a transparent flame-retardant polymethyl methacrylate composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101, mixing polymethyl methacrylate, acrylate rubber grafted methyl acrylate, flame retardant, toughening agent, coupling agent, antioxidant and lubricant in parts by mass to obtain a premix; S102, melt-extrude the premix at an extrusion temperature of 210-220° C. in a twin-screw extruder, cool and granulate to obtain a transparent flame-retardant polymethyl methacrylate composite material.
Citation Information
Cited By
Preparation method of regenerated PMMA (polymethyl methacrylate) material based on waste car lamp plastic
CN120349607A
Environment-friendly acrylate adhesive with fireproof performance and preparation method thereof
CN120554967A